More, but not of the same – new funding for a new type of AR4D needed - Loboguerrero Rodriguez, Ana María; Campbell, Bruce M.; Millan, Alberto (DLG-Verlag GmbH, 2021)
Given the ambitious targets needed to meet to transform food systems under climate change, innovation efforts need to be significantly stepped up – both in terms of innovation practice and investment volumes. New approaches to financing action in food systems are there, but they have to be linked to innovation to drive rapid transformation.